Integrated staff attendance system (ISAS) - Pek Ling, Wee (2012)
Attendance in an organization is important to ensure the continuous operation.Aiming at the disadvantages of traditional punch card attendance system, an Integrated Staff Attendance System (ISAS) is proposed.ISAS is a system used to record the present of staffs to work.It provides a customization option of using 2 input devices:smart card and fingerprint technology.Rapid Application Development (RAD) is used as it gives much faster development process which will guarantee the punctuality of the system delivery.This system allows the workers to take attendance, view their user profile and also attendance, while the manager can view workers’attendance, managing workers' information and generating attendance report.